CONTEMPORARY VIEWS ON THE TERM ‘DISCOURSE’ IN PSYCHOLOGICAL STUDIES - Taisiya A Grebenshchikova; Irina A Zachiosova; Natalya D Pavlova (RUDN Journal of Psychology and Pedagogics, 2018)
Various branches of science that study homo loquens, а talking man, have made an important contribution to the development of the term ‘discourse’. It is obvious that most definitions have much in common. Firstly, discourse is realized in speech; secondly, it is formed in a wide communicative context as a result of interpersonal communication and interactions between people and society; and finally, discourse has significant impact on social and personal representations and can establish group norms. The paper discusses different approaches to discourse studies, including speech act theory, conversational analysis, discourse analysis, social and cognitive psychology. Special attention is paid to Intent-analysis which considers the basis of discourse as a hierarchy of its speech intentions and their different psychological determinants. These include interpersonal relationships, personality traits, social statuses, roles and the problems speakers solve in the communication process. Several terms related to discourse are given: discoursive practice, discoursive thinking, discoursive abilities etc. The urgent issues of discourse research such as the typology of discourses, the psychological impact and interpersonal interaction mechanisms connected to the various fields of the current reality are presented.